2000
DOI: 10.1152/ajpheart.2000.279.2.h772
|View full text |Cite
|
Sign up to set email alerts
|

Exercise adaptation attenuates VEGF gene expression in human skeletal muscle

Abstract: Angiogenesis is a component of the multifactoral adaptation to exercise training, and vascular endothelial growth factor (VEGF) is involved in extracellular matrix changes and endothelial cell proliferation. However, there is limited evidence supporting the role of VEGF in the exercise training response. Thus we studied mRNA levels of VEGF, using quantitative Northern analysis, in untrained and trained human skeletal muscle at rest and after a single bout of exercise. Single leg knee-extension provided the acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
132
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(154 citation statements)
references
References 34 publications
(48 reference statements)
16
132
3
Order By: Relevance
“…In regard to the effects of physical exercise on VEGF levels, several studies have been conducted which have yielded contradictory results. Results of the present study revealed increased VEGF levels for sprint-endurance training groups without supplementation, which are consistent with the results of some studies 23,25,28 while different from the results of some other studies. 8,29 The specific training method applied in this study could account for such contradictory results.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In regard to the effects of physical exercise on VEGF levels, several studies have been conducted which have yielded contradictory results. Results of the present study revealed increased VEGF levels for sprint-endurance training groups without supplementation, which are consistent with the results of some studies 23,25,28 while different from the results of some other studies. 8,29 The specific training method applied in this study could account for such contradictory results.…”
Section: Discussionsupporting
confidence: 84%
“…22 Studies conducted in this field indicate that skeletal muscle capillary density, both in animal and human models, is increased in response to exercise training. 23,24 Although physical exercise can regulate serum levels of angiogenic factors, to prevent creation of pathological conditions such as arteriosclerosis and arthritis, molecular mechanism of capillary network growth in response to exercise training should be elucidated. 25 As shown in some previous studies, serum VEGF values increased after exercise, 26,28 whereas other studies reported no changes in serum VEGF levels after acute exercise.…”
mentioning
confidence: 99%
“…The surprising result of higher VEGF and VEGFR-I mRNA levels at the non-distracted side might be the result of preferable load of the non-distracted leg, since increased mechanical load leads to an increased VEGF expression [3,19,43,45]. It has been shown that VEGF mRNA expression in muscles increased by 178% after a 45 min exercise [2].…”
Section: Discussionmentioning
confidence: 99%
“…THERE IS A GROWING APPRECIATION of the concept that O 2 supply and demand limitations to maximal metabolic rate are dependent on the population studied (4,26,31). However, it should be noted that the preponderance of data have been collected from physically active or endurance-trained subjects who reveal O 2 supply dependence at maximal O 2 uptake (V O 2 max ).…”
mentioning
confidence: 99%